Czech Evangelic Congregations in Eastern and South-Eastern Europe or “They Brought the Bible with Them...” (Theatrum historiae, 2021)
This paper deals with Czech evangelic communities in Eastern and South-Eastern Europe, which claimed allegiance to reformed religion. Some of these communities are still active today. The localities under study arose as a result of the migration of the Czech population in the nineteenth century and at the beginning of the twentieth century due to economic and social reasons. Czech settlers helped populate the uninhabited peripheral parts of the Habsburg monarchy, or descendants of Czech exiles outside the monarchy established new settlements to ensure needed subsistence elsewhere at the growing number of inhabitants in original exile villages. The paper aims to describe the background to the migration of the Czech-speaking population and the historical development of Czech-speaking foreign evangelic communities of the reformed religion.
Keywords: evangelical; Helvetic Confessions; compatriot; Czech communities abroad; Poland; Ukraine; Romania; Serbia; Croatia